0
Could someone please explain this factorization questions USING the Difference of Two Squares rule.

Image at http://imgur.com/VjxAt

Notice: Undefined index: title in /home3/wmroi/public_html/merspi.com.au/qa-theme/NewMerspi/qa-theme.php on line 1251

1 Answer

0
I'm assuming you're asking about Q3 (g) because there is already a worked example for the other one.



Difference of Two Squares rule:

(x + y)(x - y)

= x^2 - xy + yx - y^2

= x^2 - y^2

so then,

x^2 - y^2 = (x + y)(x - y)



Q3 (g) 5(x + 3)^2 - 5y^2

= 5[ (x + 3)^2 - y^2 ]

= 5[ [(x + 3) + y] * [(x + 3) - y] ]

=5(x + 3 + y)(x + 3 - y)

Notice: Undefined index: title in /home3/wmroi/public_html/merspi.com.au/qa-theme/NewMerspi/qa-theme.php on line 1251